Production Of Banana Heart Waste Probiotics with the Addition of Lactobacillus sp. As A Supplement for Superior Village Chicken - Anam, Muhammad Sayyidul; Fitrihidajati, Herlina; Candra, Adi; Nurcholis, Nurcholis; Sugiyono, Sugiyono (Universitas Muhammadiyah Malang, 2026)
Banana utilization is mainly focused on the fruit, while other parts such as banana heart are often considered waste. Banana heart waste is abundant but has not been optimally utilized, even though it contains fiber, crude protein, flavonoids, tannins, vitamins, and minerals including calcium, phosphorus, and iron. Probiotics are live microorganisms that provide health benefits when administered in sufficient amounts and play important role in improving digestive health and livestock productivity, including Balitbangtan’s Superior Village Chicken. This study aimed to process banana heart waste into probiotics through fermentation using Lactobacillus sp., which functions to break down complex compounds into simpler forms and enrich metabolites. Fermentation was carried out for seven days with the addition of Lactobacillus sp. Parameters observed included microbial viability, pH, and colony morphology. Data were analyzed descriptively using quantitative methods by calculating average values and comparing them with probiotic standards. The results showed that banana heart-based probiotics had microbial viability 10⁶–10⁷ CFU/mL and pH 4.89. Colony morphology exhibited typical characteristics of Lactobacillus sp., including opaque, smooth and shiny surface, circular, flat elevation, entire margin, and diameter 2 mm. These results indicate that banana heart probiotics meet probiotic quality standards and have potential application for KUB chickens.